Associated short and regular implants for complete denture retention in an atrophic mandible: clinical follow-up/ Implantes corto y regular asociados para retención de prótesis completa en mandíbula atrófica: seguimiento clínico/ Implantes curto e regular associados para retenção de prótese total em mandíbula atrófica: acompanhamento clínico - da Silva Valente, Valdimar (2023)
Objective: to present the radiographic clinical follow-up of the prosthetic rehabilitation of a patient with an atrophic mandible, with the installation of short implants associated with an implant of regular length. Method: case report of a completely edentulous patient with an atrophic mandible and a 6-year radiographic clinical follow-up conducted at the dental clinic of the Federal University of Piauí, Teresina, from February 2011 to January 2020. After collecting sociodemographic data, health records, clinical radiographic examinations, and prosthetic surgical planning, four dental implants were installed between the mental foramina. After three months, mini-conical abutments and a fixed prosthesis screwed onto the implants were installed and monitored every six months for a period of six years. Results: the clinical evaluation revealed tissue stability without significant peri-implant changes after the follow-up period. Radiographically, bone resorption was not observed around the implant. Stability of the prosthesis and absence of prosthetic complications were observed during the follow-up period. Conclusion: short implants associated with regular-length implants can be placed in the anterior region of an atrophic mandible for rehabilitation with fixed complete dentures.